A Symmetric Cryptographic Technique to Secure Personalized Data with Chaos - G. Sravana Sai Priya, Joan S Muthu, C.Jothi Kumar ,P.Murali (International Journal of Advanced Science and Technology, 2020)
Medicinal information is stored as a database in clinics. These therapeutic databases store information that could be anything from complete body check up to lab reports and conclusions identified with the patient. Many assaults are being carried out in many companies such as network attacks where the data integrity is lost. The information that is available in the medicinal database is sensitive, confidential and the availability of this information is restricted to approved, authorized people. So, in this system we have also focussed on implementing Shannon’s Property where the property has two stages namely, confusion and diffusion. Confusion is the first stage that concentrates more on converting the text into its ASCII value. Diffusion is the second stage that takes the output of confusion and modifies the position of the encrypted text. Furthermore, the framework additionally shows that this patient-controlled encryption takes less computational time, and can be applied when immense data has to be verified.